Tooth size discrepancy: Digital vs manual measurement - Džemidžić Vildana; Nukić Velida; Tiro Alisa (Balkan Stomatological Society, 2024)
Background/Aim: The aim of this study was to determine the accuracy of overall and anterior Bolton's ratio measurements obtained with an intraoral scanner compared to standard caliper measurements on plaster models. Material and Methods: This study included 33 subjects (18 female and 15 male), aged 12 to 18 years. All subjects were taken impression for the purpose of making study plaster models. In addition, all subjects underwent intraoral scanning for the purpose of creating digital models. Tooth width was measured with a caliper on plaster models, while digital models were analyzed using Cerec Ortho SW 2.0.2 software. The overall and anterior Bolton ratios were derived using both methods. Statistical data processing was performed using an independent t-test. Results: The results obtained using these two methods for measuring the anterior and overall Bolton ratio showed that there was no statistically significant difference in the measurements obtained on plaster models and the measurements obtained by intraoral scanning. For the overall Bolton ratio, T-test was 0.828 and is not statistically significant (p<0.05). The value of T-test for the anterior Bolton ratio was 0.001 and it was also not statistically significant (p<0.05). Conclusions: Determination the overall and anterior Bolton ratio using an intraoral scanner is an accurate and acceptable method for clinical work in orthodontics.